(untitled) (Bangladesh Journal of Infectious Diseases, 2020)
Background: Covid19 virus causes pandemic worldwide. Objective: The purpose of the present study was to investigate the clinical features and imaging characteristics on chest High-Resolution Computer Tomography (HRCT) of COVID-19. Methodology: This retrospective study was conducted in the special designated department for covid-19 isolation unit under Ningxia Medical University from 10 January to 15 February 2020. The medical history, clinical symptoms, and imaging characteristics of confirmed COVID-19 patients from a single center were retrospectively analyzed. All cases underwent a chest HRCT examination. Results: A total number of 24 patients were recruited for this study of which 18 cases had clinical symptoms of respiratory tract infection; 2 cases had symptoms other than respiratory tract and 4 cases had asymptomatic. There were 15 males and 9 females aged 17 to 74 years. The main chest HRCT manifestation was diffuse ground-glass opacity (GGO) in the peripheral zone of the lungs and under the pleura. Pulmonary interstitial changes, bronchial air signs, bronchial vascular bundle thickening, paving stone signs, and "white lung" changes appeared in some cases. A few cases have enlarged lymph nodes and a small amount of pleural effusion. Conclusion: The COVID-19 has specific characteristics on chest HRCT. Bangladesh Journal of Infectious Diseases, April 2020;7(suppl_1):S3-S10